PRODUCTION TECHNOLOGY OF DOUBLE-LAYERED KNITWEAR (Spectrum Journal of Innovation, Reforms and Development, 2026)
Research on methods for producing double-layered knitted fabric with improved quality indicators, enhanced physical and mechanical properties, and reduced raw material consumption using the technological capabilities of flat knitting machines.